The influence of the design and method of short-circuit current measurement on the possibility of parallel operation of high-speed circuit breakers - Nowak, Łukasz; Borkowski, Piotr; Rojek, Artur (Archives of Electrical Engineering (Online), 2025)
This article describes various designs of high-speed DC circuit breakers used in the world and current detection methods using modern current sensor solutions. The crite-rion for selecting circuit breakers for testing was their certification for use in the European Union – the LOC&PAS TSI certificate of conformity (Commission Implementing Regula-tion (EU) 2023/1694). The possibility of parallel operation of circuit breakers from different manufacturers and different methods of switching off the short-circuit current were ana-lyzed. Tests were carried out at a 3 kV traction substation in real operating conditions of circuit breakers, which allowed us to answer the question regarding the possibility of using two different types of circuit breakers on one traction vehicle.